Characterization of Integrons and Antimicrobial Resistance in Escherichia coli Sequence Type 131 Isolates - Jiangqing Huang; Fangjun Lan; Yanfang Lu; Bin Li (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Escherichia coli sequence type 131 (ST131) is an important multidrug-resistant extraintestinal pathogen, which can cause many kinds of infections. Integrons may play a crucial role in the dissemination of antibiotic resistance genes. The purpose of this study was to characterize the prevelance of integrons among E. coli ST131 strains in China. Methods. Eighty-three E. coli ST131 isolates were used in this study. The antibiotic susceptibility test was performed by the disk diffusion method. The presence and characterization of class 1, 2, and 3 integrons, as well as promotor of gene cassettes and other antimicrobial resistance genes, were detected by PCR and DNA sequencing. Transfer of integrons was carried out using a broth culture mating method. Clonal relatedness of E. coli ST131 isolates was analyzed by PFGE. Results. Overall, 26.5% (22/83) of the E. coli ST131 isolates carried class 1 integrons. Class 2 and 3 integrons were not found in this study. Two types of gene cassette arrays were demonstrated in this study and were as follows: dfrA17-aadA5 and aac(6′)-Ib-cr-cmlA5. Only one type of Pc promoter variant was detected among 22 integron-positive isolates (PcW). In vivo transfer of integron was successful for 9 of integron-positive E. coli ST131 isolates harboring resistance gene cassettes. Results of PFGE demonstrated that the integron-positive E. coli ST131 isolates were grouped into 12 different PFGE clusters. Conclusions. Our study showed a low prevalence of integrons was detected in E. coli ST131. Continued surveillance of this mobile genetic element should be performed to study the evolution of antibiotic resistance among E. coli ST131.